2022
DOI: 10.1155/2022/4148983
|View full text |Cite
|
Sign up to set email alerts
|

Snap Bean (Phaseolus vulgaris) Response to Deficit Irrigation and Nitrogen Fertilizer and Relationships between Yield, Yield Component, and Protein Content

Abstract: Field experiments were conducted at Adami Tulu, Ethiopia, for two successive dry seasons to investigate how nitrogen levels and deficit irrigation affect the yield and its related components, and the protein content of snap beans. The treatments were deficit irrigation with three levels (50, 75, and 100% ETc) and application of nitrogen with four levels (0, 46, 92, and 138 kg·N·ha−1), which were set up as split-plot arrangement, with irrigation being as the main plot and nitrogen levels as subplot, replicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Regarding the two main nutritional traits, protein content and sugars content, the relative ranges were between 16.82% (SBP064) and 26.59% (SBP073) and between 4.27 • Brix (SBP036) and 6.40 • Brix (SBP098), respectively. The broad range of variability of protein content observed among the snap bean lines agreed with other studies [40][41][42]. Likewise, according to the literature, as well as in this study, significant differences were detected in the sugar content among the lines (Table S1).…”
Section: Characterization Of the Entire Set Of Sbpsupporting
confidence: 93%
“…Regarding the two main nutritional traits, protein content and sugars content, the relative ranges were between 16.82% (SBP064) and 26.59% (SBP073) and between 4.27 • Brix (SBP036) and 6.40 • Brix (SBP098), respectively. The broad range of variability of protein content observed among the snap bean lines agreed with other studies [40][41][42]. Likewise, according to the literature, as well as in this study, significant differences were detected in the sugar content among the lines (Table S1).…”
Section: Characterization Of the Entire Set Of Sbpsupporting
confidence: 93%
“…Delfini et al [ 23 ] reported a lower range (16.9–20.2 g/100 g) for protein content in seeds from 1512 accessions of Brazilian common bean germplasm compared to our data. The interaction between irrigation and nitrogen application during plant growth has a significant effect on protein content in French bean pods (12–18% DW) [ 24 ]. The highest caloric value among the samples was in the pods of KIS_10 and the lowest in the pods of KIS_3, but these differences were not significant.…”
Section: Resultsmentioning
confidence: 99%
“…Helium (He) was used as the reaction gas at a flow rate of 5 mL/min in He mode and 10 mL/min in HEHe mode. The isotopes monitored were 23 Na, 24 Mg, 31 P, 34 S, 39 K, 43 Ca, 55 Mn, 56 Fe, 59 Co, 63 Cu, 66 Zn, and 95 Mo. The majority of the elements were measured in the He mode, while P and S were measured in the HEHe mode.…”
Section: Multi-elemental Analysis Using Icp-msmentioning
confidence: 99%